DISTRIBUSI DAN STRUKTUR POPULASI MACROBRACHIUM PILEMANUS (DE MAN) PADA BEBERAPA ANAK SUNGAI CISADANE - FIDHIANY, LUCIA (BERITA BIOLOGI, 1985)
LUCIA FIDHIANY. 1985. Distribution andpropulation structure of Macrobrachium pilimanus (De Man) at Cisadane river. Berita Biologi 3 (3) :125 - 127. Study on spatial distribution and population structure of Macrobrachium pilimanus was conducted at Cigombong River and Cisalopa River. Based on seven habitat types in a river pool, distribution pattern of the prawn contagious.The prawn is a torrent species, because it prefers running water with gravels and stones more than stagnant one.Based on the size frequency classes, the population are bi - or polimodal for the male, and unimodal for the female. Sex ratio is equal, but the quantity of larger male is greater than female that indicate sexual dimorphism.